2022
DOI: 10.1037/neu0000830
|View full text |Cite
|
Sign up to set email alerts
|

Social cognition and competence in preschoolers with congenital heart disease.

Abstract: Objective: Children born with congenital heart disease (CHD) are at an increased risk for various neurodevelopmental impairments. However, little is known regarding social outcomes associated with CHD, particularly during early childhood. The present study aimed to characterize the sociocognitive profile and to assess the contribution of language, executive functions (EF), and social cognition to social competence (SC) in preschoolers with CHD. Method: Five-year-old children with CHD (n = 55) completed a stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 112 publications
(185 reference statements)
0
0
0
Order By: Relevance
“…While our finding that group (CHD or control) did not influence EF scores is supported by a recent study in preschool children at 5 years with CHD, which showed that parent-rated EF scores did not differ from normative means, 37 other studies have identified impaired EF at older ages in individuals with CHD. However recent meta-analyses have shown considerable between-study heterogeneity, including differences in study designs in EF assessments, and outcomes in this population.…”
Section: Discussionsupporting
confidence: 82%
“…While our finding that group (CHD or control) did not influence EF scores is supported by a recent study in preschool children at 5 years with CHD, which showed that parent-rated EF scores did not differ from normative means, 37 other studies have identified impaired EF at older ages in individuals with CHD. However recent meta-analyses have shown considerable between-study heterogeneity, including differences in study designs in EF assessments, and outcomes in this population.…”
Section: Discussionsupporting
confidence: 82%
“…These conditions are characterized by multifaceted consequences and implications that extend well beyond cardiac functionality. Research evidence showed that individuals with CHD often obtain significantly lower measures of abstract reasoning (Semmel et al, 2018), have much lower composite score means for verbal comprehension, and perform significantly worse in language tests as opposed to the general population (Cassidy et al, 2015; Gaudet et al, 2022; Wotherspoon et al, 2020). The cognitive and verbal development of children with CHD appears to be influenced by various factors.…”
Section: Introductionmentioning
confidence: 99%
“…To illustrate, delays in both social development and executive function have been repeatedly observed across infants admitted to the NICU and infants with CP [5][6][7][8][9][10]. For instance, cross-sectional studies of these highrisk infants have reported social impairments spanning from social-communicative difficulties in early childhood to social isolation and withdrawal in adolescence and adulthood [6,[9][10][11][12][13][14][15]. These delays have been found to confer lifelong challenges including decreased quality of life, relationship issues and fewer educational and vocational opportunities [16][17][18].…”
Section: Introductionmentioning
confidence: 99%